Cold Atmospheric Pressure Plasma May Prevent Oral Mucositis-Related Candidemia in Chemotherapy-Treated Rats - Sampaio, Aline da Graça [UNESP]; Milhan, Noala Vicensoto Moreira [UNESP]; do Nascimento, Fellype [UNESP]; Kostov, Konstantin Georgiev [UNESP]; Koga-Ito, Cristiane Yumi [UNESP] (MDPI, 2024)
Oral mucositis associated with candidiasis can causes systemic candidemia, posing a risk to cancer patients administered antineoplastic therapy. Cold atmospheric pressure plasma jets (CAPPJs) have antifungal and anti-inflammatory properties. This study evaluated the effects CAPPJs in preventing systemic fungal dissemination in a murine model of oral mucositis associated with candidiasis. Forty Wistar rats were divided into groups: CAPPJs (treated) and non-treated controls (for comparison), with subgroups subject to 24 and 72 h of treatment (n = 10 each). Four cycles of chemotherapy (cisplatin and 5-fluorouracil (5-FU)) were administered, followed by oral inoculation of Candida albicans for 3 days. Mucosal damage was induced on the lateral side of tongue with 50% acetic acid. CAPPJ treatment was performed on the lesion for 5 min (2 days). Body weight was assessed daily. Fungal dissemination was conducted using organ macerates and plated on Sabouraud Agar with chloramphenicol. Blood samples were obtained for blood count tests. Chemotherapy affected the general health of the animals, as evidenced by body weight loss. Treatment with CAPPJs showed an inhibitory effect on C. albicans, with a significant reduction in fungal recovery from the tongue after 24 h (p < 0.05). Interestingly, systemic fungal dissemination was significantly reduced after 24 and 72 h of treatment when compared to control (p < 0.05). Taken together, these results suggest that CAPPJs have potential for clinical application in patients with oral mucositis at risk of candidemia.
Keywords: cold atmospheric pressure plasma jets; fungemia; mucositis; plasma gases